REPRESENTASI MAKNA PESAN DAKWAH DALAM LIRIK LAGU TOMAT (TOBAT MAKSIAT) PADA ALBUM INGAT SHALAWAT KARYA WALI BAND - Devi Arie Shandy; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The development of Islamic da'wah in this day and age not only do the teachers da'wah (preachers), many media that can be used in preaching to convey the teachings of Islam, such as television, newspapers, magazines, books, the internet, and even a song. Through the lyrics written by the creator of the song, listeners are invited to interpret the brain through the store experience and knowledge, as well as the process as a basic foundation in digesting the beauty of song lyrics. Capable of causing a lot of the lyrics are strongly influenced by the perception of the level of understanding someone who comes from life experience possessed. This study aims to reveal the meaning of Islamic da'wah messages through a song by the band Guardians titled TOMAT (Tobat Maksiat) through the meanings of denotation, connotation of the lyrics of the song that is associated with the myth.The method used is that of Roland Barthes semiotic analysis assumes that the denotation and connotation of the most powerful at the end. Researchers used a form of qualitative research and interpretive approach. The subjects were the lyrics text TOMAT (Tobat Maksiat). The object of research is the meaning of denotation, connotation and myth in the lyrics TOMAT (Tobat Maksiat). In collecting the data, the researchers used a technique of documentation, library research and interviews. The data analysis techniques to be able to draw conclusions that give an overview over the data.The results of this study indicate that the lyrics of the song TOMAT (Tobat Maksiat) presented the meaning of the message propagation is seen directly from the meaning of denotation, connotation and myth in every lyric. Propaganda messages related to aqidah form values is to remember death, advising fellow, begging forgiveness for all sin, and prepare everything needed for the afterlife. Propaganda messages related to Islamic values which form the whole earth will not be eternal, and propaganda messages relating to the worship that is given the value of sin which we have done.Key words : Propaganda, Representation, Semiotics of Roland Barthes